Measurement of heat transfer coefficient distributions and flow field in a model of a turbine blade cooling passage with tangential injection - Ling, J; Ireland, P; Harvey, N; ASME (2006)
In certain regions of turbine aerofoils, cooling system designers need to cool the blades with convection systems that provide high heat transfer coefficients. The present research has investigated a circular cooling passage with tangential injection suitable for a blade leading edge. The heat transfer coefficients are measured using the conventional transient heat transfer, liquid crystal technique. The results are compared to the data from steady state experiments performed by Hedlund et al. [1]. The cooling system performance is compared in detail to average data from earlier tangential injection experiments and to local heat transfer coefficient expected from a normal impingement system. The vortex flow field was also studied by numerical prediction and near-wall velocity measurements. The investigation of the flow structure has led to understanding of flow mechanisms responsible for the high heat transfer coefficient. The vortex flow field was also investigated using computational fluid dynamics and with hot wire anemometry. The latter near wall measurements were combined with the law of the wall and Colburn analogy to validate the flow and heat transfer measurements. Copyright © 2006 by ASME.